Dose Finding Study of a Low Molecular Weight Heparin, Innohep, in Haemodialysis - Ryan, K E; Lane, D A; Flynn, A; Shepperd, J; Ireland, H A; Curtis, J R (Thrombosis and Haemostasis, 1991)
A pilot investigation was performed with Innohep, a low molecular weight (LMWH) preparation (peak maximum molecular mass 3,000-6,000), to determine possible dose regimens for patients undergoing regular maintenance haemodialysis for chronic renal failure. Results from this study suggested that suppression of macroscopic clot formation and fibrinopeptide A (FPA), a marker of fibrin formation, could be achieved following bolus injections rather than bolus injections and an infusion. On the basis of these preliminary findings, a randomised crossover study was performed in eight patients undergoing regular maintenance haemodialysis for 5-7 h to determine the effective antithrombotic dose of this LMWH. Single i.v. bolus doses of 1,250 AFXa u, 2,500 AFXa u and 5,000 AFXa u (n = 7-8) were compared to an UFH regime of 5,000 iu + 1,500 iu/h. Excessive clot formation in the dialyser bubble trap, necessitating additional UFH to enable completion of a prolonged (up to 7 h) dialysis, was observed in all patients on the 1,250 AFXa u dose (mean duration of dialysis prior to UFH, 3 h) but in a single patient only receiving the other LMWH doses. A dose-related response in the AFXa activity, measured by chromogenic substrate (CS) assay was seen in the three LMWH groups, with levels declining significantly (p <0.05) from 1-7 h. This contrasted with the constant levels maintained during dialysis with UFH. FPA levels were significantly elevated after 2 h following the 1,250 AFXa u bolus and after 4 h following the 2,500 AFXa u bolus. There was no significant difference in FPA levels between the 5,000 AFXa u bolus and UFH. β-thromboglobulin (pTG) levels rose significantly towards the end of dialysis in all LMWH groups and, at 5 h, were significantly increased following the 5,000 AFXa u and 2,500 AFXa u doses when compared to the UFH regime. AFXa levels correlated negatively with FPA levels (r = -0.62; p <0.01). In conclusion, for administration of Innohep, a bolus dose of 2,500 AFXa u would appear to be sufficient for dialyses of short duration (up to 4 h), whilst a 5,000 AFXa u bolus is as effective as UFH for a 6 h dialysis. AFXa activity measured by CS assay is related to inhibition of fibrin formation and can be used for monitoring purposes.